Isolation and Characterization of a Molybdenum-reducing and Carbamate-degrading Bacillus amyloliquefaciens strain Neni-9 in soils from West Sumatera, Indonesia (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2020)
The isolation of a molybdenum-reducing bacterium with the capacity to grow on the insecticides carbaryl and carbofuran is reported. Characterization of the bacterium was carried out using resting cells in a microtiter plate. The bacterium reduced molybdenum to molybdenum blue optimally between pH 6.3 and 6.5, between 30 and 37 oC, between 5.0 and 7.5 mM phosphate, and between 20 and 30 mM sodium molybdate. Molybdenum reduction was inhibited by silver, copper, mercury and chromium at 2 ppm by 67.6, 58.4, 57.3 and 17.4%, respectively. The bacterium was identified as Bacillus amyloliquefaciens strain Neni-9. Growth on carbaryl and carbofuran modelled according to the modified Gompertz model gave maximum specific growth rates of 1.194 h-1 and 0.913 h-1, for carbaryl and carbofuran, respectively, while the lag periods of 1.67 h and 2.63 h were observed for carbaryl and carbofuran, respectively. This is a novel molybdenum reducing bacterium showing pesticide-degrading capacity.
Keywords: Molybdenum reduction, molybdenum blue, Bacillus amyloliquefaciens, carbaryl, carbofuran